RoboCup 2015: Robot World Cup XIX - Almeida, Luis; Ji, Jianmin; Steinbauer, Gerald; Luke, Sean (Lecture Notes in Artificial Intelligence, 2015)
This book is the Proceedings of the 19th Annual RoboCup International Symposium, held in Hefei, China, in July 2015. The book contains 20 papers presented at the Symposium, carefully selected from 39 submissions. Additionally the book contains 11 champion team papers and one paper from the Workshop on Benchmarking Service Robots. The papers present current research in robotics, artificial intelligence, computer vision, multiagent systems, simulation, and other areas.